Analisis Faktor-Faktor Fundamental Rasio Keuangan Terhadap Harga Saham - Neni Marlina Br Purba; Handra Tipa (Journal of Applied Accounting and Taxation, 2020)
This research is intended to understand how the Fundamental Factors of Financial Rratios Against Share Pricees in LQ45 Companies listed on the Indonesia Stock Exchangge. Which includes fundamental factors, namely Return on Equity (ROE), Returnt on Asset (ROA), Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Current Ratio (CR), Earning Per Share (EPS). All LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2018 are the populationt. Samples were taken bye determining criteria in accordance with the research objectives. The results of the data are then proccessed using the classical assumption test. Then the hypothesis is tested by multiple linear regression test, simultaneous test (F test), partial test (t test) and determination test (R2 test). Based on the test results with the help of SPSS, it is partially obbtained fundamental factcors which include Return on Equity (ROE) and Earning Per Share (EPS) have a significant effeect on stock prices. Meanwhille, stock prices are affected but not significantly by Return on Assets (ROA), Debt to Asset Ratio (DAR), and Currennt Ratio (CR). Through a joint test, the stock price is also significantly influenced by all the variables included in the fundamental factors.